Total Synthesis of Methyl 1,5,8-Trimethoxy-1H-isochromene-3-carboxylate and Its Derivatives via Palladium-Catalyzed Annulation of 2-Alkynylbenzaldehydes - Nardangeli, Nolan; Thomson, Jared; Topolovčan, Nikola; Hudlický, Tomáš (Synthesis, 2021)
A 7-step total synthesis of methyl 1,5,8-trimethoxy-1H-isochromene-3-carboxylate and a 5-step synthesis of its C-3 derivatives are reported. Sonogashira coupling of 2-halobenzaldehydes with terminal acetylenes was employed to access 2-alkynylbenzaldehydes, which underwent a Pd-catalyzed annulation to afford the corresponding isochromene-containing products.
Keywords: 2-alkynylbenzaldehydes; antitumor agents; isochromene annulations; palladium catalysis; total synthesis